2D GEM-based SXR imaging diagnostics for plasma radiation: Preliminary design and simulations. (October 2022) - Chernyshova, Maryna; Malinowski, Karol; Jabłoński, Sławomir; Melikhov, Yevgen; Wojeński, Andrzej; Kasprowicz, Grzegorz; Fornal, Tomasz; Imríšek, Martin; Jaulmes, Fabien; Weinzettl, Vladimir
Highlights: Development of novel 2D X-ray imaging system for 3D tomography for plasma radiation. Tokamak plasma tangential view, new data for toroidal phenomena observations. Simulations of GEM internal structure. Simulations of spatial and spectral radiation distributions for COMPASS Upgrade. Dedicated data acquisition system for gaseous detectors. Abstract: The purpose of this research is to design and construct a plasma radiation imaging system for fusion devices which is focused on soft X-ray region from about 2 to 15 keV photon energy. The proposed 2D diagnostic system, as opposed to conventional 1D systems, is expected to benefit from tangential field of view and to deliver new data for toroidal phenomena observations. This contribution relates to the introductory development of such 2D system laying out details on the overall design of the detecting unit (based on GEM technology) as well as on its acquisition module. The results cover also the expected photon flux and spectra foreseen for COMPASS-U device, as a first choice for testing and verification. Considerations on working medium and internal structure of the detecting sensor are presented including electrodes configurations and collecting electrode pattern. The preliminary establishments for data acquisition system are presented as well.